A REVIEW ON PHYSICO-CHEMICAL PARAMETERS OF LIPOSOMAL DOXORUBICIN - SINGH, DEEPANMOL; PAHWA, SHILPA (International Journal of Applied Pharmaceutics, 2020)
The development of a generic liposomal doxorubicin product requires the study of critical physicochemical properties of the formulation. Food and Drug Administration (FDA) draft guideline has suggested few parameters to be tested for in vitro bioequivalence study which include liposomal composition, state of encapsulated drug, internal environment, liposomal morphology and number of lamellae, lipid bilayer phase transition, liposomal size distribution, grafted Polyethylene Glycol (PEG) at liposomal surface, electric surface potential or charge and in vitro leakage under multiple conditions. Characteristic features of components of liposomal doxorubicin formulation and detail of parameters to be studied have been discussed. This review compile specific, current and historical research outcomes on in vitro analysis of liposomal doxorubicin and highlights the important features that have a critical impact on properties of liposomal doxorubicin formulation. It will provide a better insight to the generic manufacturers and will help them to identify the critical quality attributes during the formulation development phase.